If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(2x + -1) = 68 Reorder the terms: -4(-1 + 2x) = 68 (-1 * -4 + 2x * -4) = 68 (4 + -8x) = 68 Solving 4 + -8x = 68 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -8x = 68 + -4 Combine like terms: 4 + -4 = 0 0 + -8x = 68 + -4 -8x = 68 + -4 Combine like terms: 68 + -4 = 64 -8x = 64 Divide each side by '-8'. x = -8 Simplifying x = -8
| 6x+7y=3230000 | | 2n-5n-15=-42 | | 5(z-2)+15=45 | | 6(x+7)=16 | | 12x^2-3+5x=0 | | 5-3b=17 | | .3x-x=252 | | (8x+4)+(5x-6)=180 | | 2(2b-5)+3=10 | | -3x-y=-25 | | -1.25+0.15x=10000000 | | 12x-3=5x | | 3x+4y=59 | | 0.12+-0.6=-0.06 | | lg(10x^2)lgx=1 | | 9y-47=t+73 | | ln(25x)-ln(x-1)= | | b^2+3=2 | | -4x-7y=-12 | | 3+5+6+9=23 | | n^2=38 | | 15b=1.5 | | n^2-19=-3 | | 5x^2+15x+15=5 | | 32timesn-435=179 | | 3k^2+48k+192=0 | | 9b-2=8 | | 6x-5(2x-1)=5x+17 | | y-120=60(x-2) | | 300=m+100 | | sqrt(x-4)+sqrt(2x-7)=5 | | 2.6666666666666=18 |